Understanding teaching and learning in primary education - Mike Carroll;Margaret McCulloch ([Place of publication not identifed] : [publisher not identified], 2014)
This textbook gives you guidance and insights into the knowledge, values and commitments necessary to succeed in the primary classroom, supported by links to theory and research literature and realistic scenarios you may encounter as a new teacher.
Chapter1. The context for primary education in the twenty-first century -- Chapter2. Childhood and diversity -- Chapter3. early years education -- Chapter4. Models of teaching and learning -- Chapter5. Planning for learning and teaching in the primary classrooms -- Chapter6. Social and emotional context -- Chapter7. Identity, relationship and behavior -- Chapter8. Developing a capacity for learning -- Chapter9. Collaborative learning -- Chapter10. interdisciplinary learning ...
Includes bibliographical references and index.
Keywords: PRIMARY EDUCATION